The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1093/joc/55.2.366
|View full text |Cite
|
Sign up to set email alerts
|

Beneath the Veneer of Fragmentation: Television Audience Polarization in a Multichannel World

Abstract: This study reviews the history of television audience fragmentation in the United States and uses a secondary analysis of Nielsen peoplemeter data to assess the current state of both fragmentation and audience polarization across 62 of the most prominent television networks. Audience fragmentation is more advanced than is generally recognized. Polarization, the tendency of channel audiences to be composed of devotees and nonviewers, is also evident, though modest. Contrary to the "law of double jeopardy," ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(128 citation statements)
references
References 1 publication
2
116
0
10
Order By: Relevance
“…It has been widely observed that over the past 20 years, the television audience has become fragmented (Webster, 2005). Average prime-time ratings on major networks are now in the single digits, and ratings on lesser networks are lower still.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely observed that over the past 20 years, the television audience has become fragmented (Webster, 2005). Average prime-time ratings on major networks are now in the single digits, and ratings on lesser networks are lower still.…”
Section: Discussionmentioning
confidence: 99%
“…Small average ratings leave little room for below average ratings to vary (i.e., they cannot dip below 0). High program ratings are increasingly rare as networks target narrower demographics, and audiences exclude networks from consideration by virtue of limited channel repertoires or "defacto selectivity" (Webster, 2005). Whatever the cause, variation in network program shares seems to have diminished over the years (McDowell & Dick, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Deste modo, se, por um lado, o aumento do número de media está provocando uma fragmentação das audiências (Webster, 2005), por outro, as ferramentas de comunicação digital parecem providenciar um mecanismo de retorno e ligação entre elementos aparentemente dispersos. Tendo em conta o estudo em apreço, atualmente, no cenário de abundância mediática, os múltiplos centros e canais autônomos existentes parecem estar ligados, num fluxo que Holton (2010: 19) designa por "convergent fragmentation".…”
Section: Em Pautaunclassified
“…In an increasingly fragmented audience environment (Napoli, 2001;Webster, 2005), the ability to offer convenient and cost-effective access to particular audiences sub-groups represents a clear strength for the magazine publishing sector.…”
Section: Fhm P4mentioning
confidence: 99%